Modelling soil organic carbon sequestration under crops for biofuels in Poland - Krasuska, Ewa; Faber, Anton; Jaros, Zuzanna; Kaczyński, Radosław (Polish Journal of Agronomy, 2023)
The soil organic carbon (SOC) stocks have become of special importance for sustainable biofuels production. We focused on SOC changes in high activity clay soils in Poland un- der arable crops for biofuels production. The SOC sequestration values were calculated using a DNDC model with four different tillage systems. The initial SOC stocks in Poland were highly spa- tially variable with values in the range of 35–97 t C ha-1 . The sim- ulated regional SOC sequestration rates in topsoils ranged from -0.17 to 0.32 t C ha-1 year-1 in full tillage, 0.36–0.73 t C ha-1 year-1 in reduced tillage, and 1.69–3.22 t C ha-1 year-1 in no-tillage. For full tillage with straw incorporation the results for SOC seques- tration were similar to those of the reduced tillage. The uncertain- ties of the estimations were provided, in addition to the length of the periods of SOC sequestration. The results for Poland are relatively high comparted to those from literature which might suggest that DNDC overestimated the SOC stocks in our study. Although DNDC was based on long-term tests and proved ad- equate SOC simulations in many studies, still a comprehensive model validation is required in a field scale with relevant SOC measurements, climatic, soil and crop data.